2013
DOI: 10.1038/onc.2013.512
|View full text |Cite
|
Sign up to set email alerts
|

The deubiquitylase Ataxin-3 restricts PTEN transcription in lung cancer cells

Abstract: The phosphatidylinositol-3-kinase (PI3K) pathway is commonly hyperactivated in cancer. One mechanism by which this occurs is by silencing of the phosphatase and tensin homolog (PTEN), a tumor suppressor and major antagonist of the pathway, through genetic, epigenetic or posttranscriptional mechanisms. Here, we used an unbiased siRNA screen in non-small-cell lung cancer cells to identify deubiquitylases (DUBs) that have an impact on PI3K signaling by regulating the abundance of PTEN. We found that PTEN expressi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
52
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 68 publications
(54 citation statements)
references
References 54 publications
2
52
0
Order By: Relevance
“…These results further confirmed the tumor‐suppressive role of PTENp1 . These findings were in line with previous studies involving lung cancer . Furthermore, PTENp1 overexpression could rescue the growth promoting, colony formation, cell‐cycle acceleration, and growth of xenografts by virtue of miR‐21.…”
Section: Discussionsupporting
confidence: 91%
“…These results further confirmed the tumor‐suppressive role of PTENp1 . These findings were in line with previous studies involving lung cancer . Furthermore, PTENp1 overexpression could rescue the growth promoting, colony formation, cell‐cycle acceleration, and growth of xenografts by virtue of miR‐21.…”
Section: Discussionsupporting
confidence: 91%
“…HAUSP (also known as USP7) specifically removes the monoubiquitylation of PTEN and induces its nuclear export but has minimal effect on PTEN protein stability 22 . The Josephinfamily ataxin-3 regulates PTEN transcript abundance but not the protein stability 23 . A recent study, through a screen of 30 USP members, identified USP13 as a candidate that de-polyubiquitylates and stabilizes PTEN (ref.…”
mentioning
confidence: 99%
“…The regulation of the basal level of chaperones may underlie the transcription factor activity of ataxin-3. As previously reported, ataxin-3 could function as a transcription factor to promote or inhibit target gene expression (Araujo et al, 2011;Evert et al, 2006;Li et al, 2002;Sacco et al, 2013). Therefore, down-regulation of chaperone expression may be due to a deficiency in transcriptional activation in mutant ataxin-3, though reports have suggested a similar activity of pathogenic ataxin-3 with 80Q and WT ataxin-3 toward modulation of expression from the hsp70 promoter (Reina et al, 2012).…”
Section: The Chaperone Systemmentioning
confidence: 75%